Novel crystal forms of Entresto: a supramolecular complex of trisodium sacubitril/valsartan hemi-pentahydrate - Shaikh, Tabrez R.; George, Christy P.; Bhukya, Priyanka; Shelke, Nikita; Pawar, Komal; Garai, Abhijit; Dandela, Rambabu; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2022)
Entresto is a salt-cocrystal supramolecular complex with the chemical name trisodium sacubitril/valsartan hemi-pentahydrate for treating chronic heart failure and was approved by the US FDA in 2015. This multidrug complex was synthesized in our laboratory to investigate its polymorphic behavior. Different crystallization conditions, including various solvent systems, yielded different novel solid forms of Entresto (Form-I to Form-VI), including the reported form. All the novel solids are solvent-dependent and were reproducibly crystallized on a 10 g scale quantity. The 1H NMR spectra confirmed the 1 : 1 stoichiometry of the two drugs, namely, sacubitril and valsartan, in all the solid forms of the crystalline products. Powder X-ray diffraction and DSC analysis of the crystalline solids established that they are distinct crystalline forms. Stability studies under ambient conditions carried out over a one-year period showed higher stability for Form-I and Form-III compared to the other forms, including the innovator crystal form (labelled as Form-II). The novel crystal forms (notably Form-I and Form-III) exhibit higher stability and less hygroscopicity than the reported Form-II.

Multicomponent solvate crystals of 3,5-dinitrobenzoic acid and acetamide and CSD analysis of solvates - Shaikh, Tabrez Rafique; Shelke, Nikita; Tothadi, Srinu (ACS Omega, 2023)
Twelve multicomponent solvate crystals (cocrystal solvates) of 3,5-dinitrobenzoic acid and acetamide were synthesized via slow evaporation method. All crystalline materials were characterized by single-crystal X-ray diffraction. All cocrystal solvates are isostructural, and crystal packing forms continuous channels where some solvent molecules are connected via weak intermolecular interactions with 3,5dinitrobenzoic acid and acetamide. All multicomponent solvate crystals encompass amide-amide dimer homo synthons and form R22 (8) motifs. Moreover, the phase purity of solvate crystals was analyzed by powder Xray diffraction. Further, most of the cocrystal solvates were analyzed by nuclear magnetic resonance and differential scanning calorimetry. Cambridge structural database analysis categorizes solvate propensity in single-crystal structures. The importance of hydrogen bond donor/ acceptor nature, size, and shape of solvents is also discussed in the context of crystallization and crystal packing.
Keywords: Co-Crystals; Design; Host Guest Complex; solvent

Exploring novel cocrystals of milrinone: a cardioprotective drug combined with nutraceuticals and an NSAID - Kenguva, Gowtham; Rekha Rout, Smruti; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CrystEngComm, 2024)
Milrinone is a bipyridine phosphodiesterase (PDE) inhibitor of the second generation. It's a PDE-III antagonist that raises cAMP levels to support heart function and acts as a systemic vasodilator in chronic decongested cardiovascular illness. It is categorised as class II in the Biopharmaceutics Classification System (BCS), indicating that it exhibits poor aqueous solubility and high permeability. Three new cocrystals of the cardioprotective drug milrinone (MR) with two nutraceuticals, e.g. sesamol (SES) and resveratrol (RES), and an anti-inflammatory drug, e.g. niflumic acid (NIF), were successfully synthesised using mechanochemical and solution crystallisation techniques. Thermal analysis (DSC and TGA) and diffraction tools (PXRD and SCXRD) were used to obtain structural insights into all the cocrystals. Their crystal structures indicate that the dimeric interactions in MR are preserved in the crystal structures in addition to carboxylic acid/phenol & ctdot;pyridine heterosynthons. Among the three synthesized molecular solids, MR.SES was more soluble than the native drug. The solubility of the cocrystals was correlated with polar surface contacts, the solubility of the coformer and melting points (inversely). We believe that the new MR.SES cocrystal offers a novel approach to enhance the drug's solubility, which may have a positive impact on its synergistic cardioprotective effects.

Structural insights into ketanserin salts with aliphatic acids and their physiochemical properties - Kenguva, Gowtham; Rout, Smruti Rekha; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CRYSTENGCOMM, 2024)
Keywords: PHARMACEUTICAL COCRYSTAL; SEROTONIN; SHYDROCHLOROTHIAZIDE; solubility

Synthesis, characterization and theoretical investigations of the newly developed molecular salts of an anti-psychotic drug (Penfluridol) - Kenguva, Gowtham; Rout, Smruti Rekha; Kar, Ananya; Giri, Lopamudra; Mahapatra, Sanat Kumar; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Dandela, Rambabu (Journal of Molecular Structure, 2025)
Penfluridol (PEN) is a clinically relevant antipsychotic medication used to treat schizophrenia; nevertheless, its bioavailability is limited due to its poor solubility. To address this issues, new molecular salts of PEN are being produced utilizing an array of GRAS (Generally Recognised AS Safe) salt formers such as oxalic acid (OXA), malonic acid (MAL), maleic acid (MAE), and an artificial sweetener (saccharin (SAC)). A variety of solid-state analytical techniques were used to identify and characterize the resulting molecular salts. Moreover, PEN and its novel salts' solubility were assessed using high-performance liquid chromatography (HPLC) and the data revealed that among all the adducts PEN.MAL exhibited a significantly higher solubility which is similar to 15 times more than the parent drug PEN. Furthermore, in order to enhance comprehension of the hydrogen bonding interaction, the Hirshfeld surface (HS), frontier molecular orbital (HOMO-LUMO), non-covalent interaction plots (NCIs), and electrostatic potential maps (ESP) investigations are discussed. Additionally, the stability of the synthesized adducts was evaluated over a 2-week period under accelerated humidity (90 % +/- 5 % RH, 40 +/- 1 degrees C) and it was observed that all the adducts demonstrated excellent stability. In light of the aforementioned observations, we expect that the latest discovery will be a superior alternative for refining and strengthening the pharmacological features of PEN.
Keywords: Anti-psychotic drug; Hydrogen bond; Liquid-assisted grinding (LAG); solubility